2022
DOI: 10.1186/s12891-022-05221-z
|View full text |Cite
|
Sign up to set email alerts
|

Syndesmotic instability can be assessed by measuring the distance between the tibia and the fibula using an ultrasound without stress: a cadaver study

Abstract: Background Ultrasound examinations for syndesmosis injury might be useful for the quantitative evaluation of syndesmotic instability. The purpose of this study was to evaluate the efficacy of ultrasound assessment by measuring the tibiofibular distance of syndesmosis injuries in various ligament-injured models and stress load conditions. Methods Five normal ankles from Thiel-embalmed cadavers were used. Ultrasound assessment was performed by placin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The TFCS-opening values detected in this study using P-US are similar to those found by Xenos et al and Shoji et al, who also evaluated the tibioibular diastasis after sequential transection of the syndesmosis [36,43]. The study by Xenos et al evaluated TFCS-opening under an external rotation torque of 5 Nm but using a Storz calliper instead of ultrasound and detected a tibioibular opening of 1.3 (AITFL), 3.5, (IOL), and 6.3 mm after the PITFL cut as opposed to the unloaded, intact stage [43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The TFCS-opening values detected in this study using P-US are similar to those found by Xenos et al and Shoji et al, who also evaluated the tibioibular diastasis after sequential transection of the syndesmosis [36,43]. The study by Xenos et al evaluated TFCS-opening under an external rotation torque of 5 Nm but using a Storz calliper instead of ultrasound and detected a tibioibular opening of 1.3 (AITFL), 3.5, (IOL), and 6.3 mm after the PITFL cut as opposed to the unloaded, intact stage [43].…”
Section: Discussionsupporting
confidence: 90%
“…The study by Xenos et al evaluated TFCS-opening under an external rotation torque of 5 Nm but using a Storz calliper instead of ultrasound and detected a tibiofibular opening of 1.3 (AITFL), 3.5, (IOL), and 6.3 mm after the PITFL cut as opposed to the unloaded, intact stage [ 43 ]. Thereby, shoji et al already found a significant widening of the tibiofibular distance after the AITFL cut with external rotation stress using ultrasound [ 36 ]. The correlation between ultrasound studies and direct measurement techniques highlight the opportunity to evaluate the syndesmosis noninvasively at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…With an external rotation stress applied, the tibiofibular distance increased by 2.0 mm after sectioning the AITFL alone ( P = 0.015). 22 While the results are promising, US has not been directly compared with other modalities or with arthroscopic evaluation.…”
Section: Imagingmentioning
confidence: 99%
“…85 Ultrasound is another modality recommended for diagnosing syndesmotic instability as it can be easily performed in outpatient and bedside settings, is minimally invasive and allows the possibility of dynamic evaluation without radiation exposure. 86 Although dynamic ultrasonographic examination showed a 100% sensitivity and specificity, 87 unfortunately it has the drawback that it cannot detect associated injuries and is investigator-dependent. 22
Figure 4.On the magnetic resonance coronal image, the lambda sign is marked by the red arrow.
Figure 5.Magnetic resonance axial image showing the ring of fire sign (marked by red arrow).
…”
Section: Investigationsmentioning
confidence: 99%